Development of Basic Tissue Histology Atlas to Improve Student Motivation and Learning Outcomes on Animal Tissue Structure Materials in High School - Anik Rahmawati; Lisdiana , (Journal of Biology Education, 2023)
This study aims to characteristics, validity, applicability and effectiveness of Basic Tissue Histology Atlas to improve student motivation and learning outcomes. This research design is Research and Development (R&D) with reference to Sugiyono's development model. The research subjects were students of class XI SMA Negeri Gondangrejo, with 30 students in the small-scale trial and 35 students in the large-scale trial. Methods of data collection in the form of media and material validation questionnaires, teacher and student response questionnaires, learning motivation questionnaires, and tests totaling 20 multiple choice questions. The results showed that the Basic Tissue Histology Atlasthat was developed obtained an average percentage of 92.2% with very valid criteria, 95% teacher responses and 100% student responses with applicable categories, 82.8% learning motivation with motivated categories. and highly motivated, as well as an increase in learning outcomes of 0.67 in the medium category. Based on the results of the study, it can be concluded that the Basic Tissue Histology Atlasthat was developed has characteristics that can be seen from each component of the atlas and a systematic and full color display, valid to be used as a learning medium in high school, can be applied as a learning medium, and is effectively used to improve student motivation and learning outcomes.